Disseminated strongyloidiasis in patients on immuno-suppressive therapy - Kodiyerithodi, Insaf; Moideen, Shamsudeen; Hafeeq, Benil; Gopinathan, Jyothish Chalil; T., Bhagyanath (International Journal of Research in Medical Sciences, 2024)
Strongyloidiasis is a disease that causes significant morbidity and rarely mortality in immunocompromised patients. We report two cases of disseminated strongyloidiasis infection while on steroids. The first patient was a known diabetic, hypertensive, and coronary artery disease who began on steroids with hemodialysis for biopsy-proven rapidly progressive glomerulo nephritis (RPGN). He presented to the emergency department (ED) with fever, loose stools, worsening dyspnea on exertion, cough, conjunctival congestion, and bilateral lower limb pain of 1-week duration while on hemodialysis (HD). He was started on intravenous (IV) antibiotics, suspecting a catheter-related septicemia. Stool and sputum examination revealed strongyloid infection. The patient was treated with Albendazole, Ivermectin, empirical antibiotics, and tapering and stopping of steroids. Symptoms improved and the patient was discharged in stable condition. The second case is a known case of systemic hypertension and biopsy-proven IgAN on maintenance steroids, with recently detected diabetes mellitus. He presented to the ED with tiredness, fever, cough, dyspnea, and occasional hemoptysis of 1-week duration. On evaluation, he had maculopapular rash over the chest and abdomen, along with hypoxia requiring oxygen support, thrombocytopenia, and worsening renal function. He was initially started on IV antibiotics, suspecting a lower respiratory tract infection with sepsis. Bronchoalveolar lavage (BAL) cytology yielded strogyloid larvae. The patient received ivermectin along with empirical IV antibiotics and supportive treatment but succumbed to the infection. These case reports signify the need for an active search for opportunistic infections in patients who are on continuous immunosuppressive therapy.